Expanding existing tourism redress mechanism to include tourism courts in West Malaysia for the protection of consumers [White paper] - Ramli, Noriah; Zawawi, Majdah; Abas, Afridah; Azmi, Ida Madieha (2019)
This White Paper is prepared with the objective of seeking the necessary endorsement from the Ministry of Tourism. Arts and Culture, Malaysia to adopt the proposals made in this White Paper for a uniformed tourism redress mechanism which includes the establishment of Tourism Courts not only in East Malaysia but also the Northern region, Central Region and Southern region of West Malaysia.